Representasi Peran Gender dalam Novel “Perempuan di Titik Nol” Karya Nawal El-Saadawi - Anggi Mesrawati Zebua; Mastawati Ndruru; Noibe Halawa; Yanida Buulolo (Badan Penerbit STIEPARI Press, 2025)
The novel Perempuan di Titik Nol is a literary work that explicitly discusses the issue of gender injustice experienced by women in a patriarchal society. This novel tells the story of Firdaus, a woman who lives in poverty and experiences various forms of oppression, from sexual violence to economic exploitation.This study aims to describe the representation of gender roles and building elements in the novel